Artikel Review: Tanaman yang Memiliki Potensi sebagai Antikanker Payudara - Isybillah Ahmad, Afifah; Sulaeman, Agus; Suri Darmawan, Ammar; Yayuk Febriyanthi , Anggita; Novia Adiningsih, Arum; Malik Al Akbar, Ayatullah; Akbar Rulazi, Bagus; Larson Boling Sau, Barth; Adinda, Deistha; Eka Cahyani, Dhiana; Yunita, Dilla; Asherlia, Dwita; Ernawati, Ernawati; Hossanti Ntobu, Febri (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: This study examines the role of pharmacotherapy in immune system diseases and cancer, highlighting the potential of natural compounds as anticancer agents. This study reviews various studies using in silico, in vitro, and in vivo approaches to activate the anticancer activity of various plant extracts and bioactive compounds. Method: This article review uses references obtained from database searches with online search instruments published nationally and internationally. Result: The results of the analysis showed that natural compounds contribute to the inhibition of cancer cell growth through apoptosis mechanisms, antioxidant activity, and reduction of inflammation. Various molecular pathways such as HER2, survivin, EGFR, Nrf2-Keap1, and PI3K/AKT/mTOR are the main targets in the development of natural compound-based therapies. The evidence collected shows that natural compounds have great potential as safer and more effective innovative cancer therapies. Conclusion: 13 plants were found to have the potential as anticancer agents in breast cancer therapy, with mechanisms of action including apoptosis induction, inhibition of cancer cell proliferation, modulation of the immune system, and regulation of molecular signaling pathways.